Porous membranes for ballast water treatment from microalgae-rich seawater. Issue 2 (30th December 2015) - Guilbaud, Julie; Massé, Anthony; Wolff, Francois-Charles; Jaouen, Pascal
Abstract: The ballast waters from ships pose a major threat to oceans, notably because of the spread of microorganisms. The present study evaluates the techno-economic feasibility of implementing the membrane process to remove microalgae from seawater to be ballasted in a single step during planktonic bloom. The optimal conditions for the microfiltration of complex and reproducible synthetic seawater are a permeate flux and specific filtered volume of 100 L.h − 1 .m − 2 and 75 L.m − 2 .cycle − 1, respectively. Recovery of the membrane process represents about 76.6% and 62.7% of the annual cost for a cruise ship (5400 passengers) and liquefied natural gas (LNG) carrier (75, 000 m 3 of liquid natural gas), followed by the membrane replacement cost (13.4% and 21.9%, respectively). The treatment costs are competitive with conventional treatments, even when the membrane process is more feasible for cruise ships due to its smaller capital cost and footprint. Graphical abstract: Highlights: The optimal conditions for microfiltration are 100 L.h − 1 .m − 2 and 75 L.m − 2 .cycle − 1 . Complete removal of microalgae was achieved by microfiltration. The feasibility of the membrane process for large-scale cruise ships and liquefied natural gas (LNG) carriers More than 62% of the total cost of membrane plants is assigned to amortization. The membrane process in cruise ships has the smallest capital cost and footprint.